Biomaterials - Vizureanu, Petrică; Manuela Da Cunha Ferreira Botelho, Claudia (IntechOpen, 2020)
This book provides an overview of biomaterials science with a focus on health and medical applications that can be improved with new biomaterials with non-allergenic elements. These materials are designed to meet functional requirements and overcome the disadvantages of classical alloys used as biomaterials in human tissue. Over seven chapters, this volume explains the problems created by classical alloys and examines how the new generation of biomaterials helps both doctors and patients. It is designed for students, doctors, patients, and researchers worldwide.